Late surgical ventricular septal defect closure in a low middle-income country setting: a case series - Zawadi Edward Kalezi; Naizihijwa Majani; Alphonce Nsabi Simbila; Stella Mongella; Godwin Godfrey Sharau; Deogratias Nkya; Sulende Kubhoja (Journal of Medical Case Reports, 2023)
Abstract Background Ventricular septal defect (VSD) is the commonest type of congenital heart lesion accounting for up to 40% of congenital heart defects. Well timed VSD closures are reported to yield excellent long-term outcomes. Late surgical VSD closures, particularly from the developing countries, are infrequently reported. Case presentation We report three cases of African children aged between 13 and 14 years who had late VSD presentations. They reported complaints of growth failure and recurrent respiratory infections since early infancy which necessitated frequent visits to primary health care facilities. They were found to have large ventricular septal defects by thoracic echocardiography. Diagnostic cardiac catheterization was done to all three patients to rule out irreversible pulmonary hypertension. After promising cardiac catheterization findings, they all underwent successful surgical VSD repair with good early outcomes. Conclusion VSD surgical closure is ideal in children below 2 years, however, it can be done in children who present at advanced age despite being considered high risk patients. All three of our patients who presented late had successful surgical VSD repairs with promising immediate outcome. The role of genetics in the protection against developing irreversible pulmonary vascular disease in these patients is a possible area for future studies.